PERUBAHAN KEPEMIMPINAN PARABELA PADA MASYARAKAT SIOMPU KECAMATAN SIOMPU KABUPATEN BUTON SELATAN - Tasrin Tasrin; Syamsumarlin Syamsumarlin; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aims to examine and describe the parabela leadership system and its changes in the Siompu community, Siompu District, South Buton Regency. This study uses the Kinship Theory of Thomas Hylland Eriksen. It uses ethnographic methods through qualitative data. The results of this study indicate that the parabela leadership system is a leader in the Siompu community that has authority and authority to protect and protect the community in general. The Parabela leadership system has reached its heyday in the era of the Buton Sultanate. However, over time with the development of the state leadership system, the system of leadership began to lose its role. The only role currently held by Parabela is as the highest leader in indigenous organizations. The parabela leadership system which is currently the top leader in indigenous organizations needs to be considered both in terms of change and in terms of the development of its leadership system. This is because indigenous organizations are a social organization that is expected to be able to bring cultural values to life. By that, all elements of the Siompu community, both upper class and lower class and related parties must contribute and support the change and development of the parabela leadership system.